Editorial: Social media use in children and adolescents: on the good or the bad side of the force? - Kaess, Michael (Child and adolescent mental health, 2020)
Children and adolescents spend increasingly large parts of their social life connecting with each other via social networks sites. While this is clearly an achievement and may have helped many of them during difficult COVID-19 lock downs, there is an ongoing political and scientific debate around the potential harm that (excessive) social media use may pose on young individuals. This editorial highlights a systematic review that was published on the topic of social media use and child and adolescent mental health, and sets the results of this review into a current research and public health perspective.